ANALYSIS OF THE ROLE OF INTERPERSONAL COMMUNICATION IN FORMING THE CHARACTER OF GEN Z IN THE DIGITAL ERA - Marpaung, Syafri Fadillah; Juliani, Duwi; Pasaribu, Gusti Aprilia; Hakim, Maulana; Adinda, Nazla Sofi (Yayasan Amanah Nur Aman, 2025)
This article examines the role of interpersonal communication in the context of Generation Z (Gen Z), the generation born after 1995 and growing up in the digital age. Gen Z, the first generation to grow up in the digital age, exhibits varying preferences for digital media depending on the context. However, they still view interpersonal communication as a crucial element in socializing. Utilizing qualitative methods and drawing on literature from journals, books, and previous research, this study investigates the shift in interpersonal communication behavior of Gen Z in the digital media landscape. Findings indicate that Gen Z actively engages in interpersonal communication through social media and digital platforms to interact, share creative content, and build social relationships. This has resulted in a shift in communication behavior from active to passive, increased self-expression through digital media, a shift in perspectives on face-to-face communication, and a decline in face-to-face communication. This article provides insight into the role of interpersonal communication in Generation Z, highlighting the shift in interpersonal communication behavior in the digital media era.